Peripheral neurotransmitters in the immune system. Issue 19 (February 2021) - Chen, Chien-Sin; Barnoud, Coline; Scheiermann, Christoph
Abstract: The nervous system exerts potent control over the immune system. A wealth of recent data strongly implicate different branches of the peripheral nervous system in toning immunity, including the sympathetic and parasympathetic as well as the sensory nervous system. Neurotransmitters released by peripheral nerves mediate the interactions with the immune system, which can have pro-or anti-inflammatory effects. In this review, we focus on these recent developments by discussing the effects of norepinephrine, acetylcholine, VIP, NMU, CGRP, substance P as well as dopamine on immune cells.